ANALYSIS OF MINERALS IN CEMPAKA-MADU GEMSTONE FROM ACEH INDONESIA BY USING XRF - Ismail .; Akmal Nizar; Mursal . (Jurnal Natural, 2018)
Abstract. Cempaka-madu is a local name for one kind of gemstone from Aceh province in Indonesia. It is so attractive and its color is dark-orange. We have utilized X-Ray Florescent (XRF) to study these cempaka-madu gemstones from Aceh Tengah and Nagan Raya districts in Aceh province. Our results show that the cempaka-madu gemstone from Nagan Raya district contains 84.90% of SiO2, 8.89% of NiO, 5.47% of Fe2O3, and 0.6% of CaO. The mineral contains in cempaka-madu gemstone from Aceh Tengah district is about the same as those from Nagan Raya district. It is found that the oxide compounds contained in the cempaka-madu gemstone is significantly different than that in jadeite, nephrite-actinolite, nephrite-tremolite, serpentine-clinochrysotile, serpentine-antigoride, and vesuvianite. Consequently, we conclude that the cempaka-madu gemstone from Aceh Indonesia cannot be categorized as jade. Keywords: cempaka-madu gemstone, jade, jadeite, nephrite, serpentine, vesuvianite